STRESS RELATED ORAL DISEASES- A RESEARCH STUDY - T.N.UMA MAHESWARI; N.GNANASUNDARAM (International Journal of Pharma and Bio Sciences, 2010)
Stress is defined as a physical, mental or emotional response to events that causes bodily or mental tension. Every organ in the human body is affected by various types of diseases like infection caused by microbes, immunological, metabolic, endocrinal disturbances etc., Etiopathogenesis of many diseases are discovered and managed at any early stage, still some diseases are considered as idiopathic, hence diagnosis and treatment plan of such diseases always becomes controversial. Stress is one such etiology or predisposing factor in many diseases. Many authors have proved stress in relation to hypertension, gastric ulcer and diabetes mellitus. Similarly this research study aims in identifying and proving the role of stress as one of the etiological factor in few oral lesions such as Oral lichen planus, Apthous ulcers, Burning mouth syndrome and Myofacial pain Dysfunction syndrome.